Perilaku Konsumtif Mahasiswa Berbelanja Melalui Aplikasi Belanja Online dalam Perspektif Ekonomi Syariah - Dwi Putri Agustini; Hilda Hilda; Ria Agustina (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Consumptive behavior is an activity in consuming goods and services that is carried out unplanned, exceeding limits and prioritizing wants over needs. This online shopping application really helps students to order the products they need and want just by making transactions on their cellphones. In the view of Islamic economics, consumptive behavior is prohibited and the prohibition has been explained in the Al-Qur'an and Hadith. This study aims to determine the Islamic economic perspective on consumptive behavior in shopping through online shopping applications for students of the Faculty of Islamic Economics and Business, UIN Raden Fatah Palembang. This type of research is a type of descriptive qualitative research using data collection methods in the form of interviews and documentation. Data analysis techniques used are data reduction, data presentation, and data verification. The results of this study reveal that the consumptive behavior of students of the Islamic Faculty of Economics and Business UIN Raden Fatah Palembang in shopping through online shopping applications still occurs in the student environment due to various reasons and in the Islamic economic perspective, consumptive behavior is prohibited and the prohibition has been explained in the Al-Qur'an and Hadith.